Kemampuan Manajerial Kepala Madrasah dalam Pengambilan Keputusan Pendidikan Islam - Sadidah Qurisma Qosfaroh; Mohammad Muhtadi; M. Kurniawan Ch (ALSYS, 2026)
The managerial capability of madrasah principals plays a strategic role in determining the quality of governance and the effectiveness of decision-making in Islamic educational institutions; however, decision-making practices that are fully grounded in musyawarah (consultative deliberation), rational analysis, and emotional stability of leaders remain suboptimal in many madrasahs. This study aimed to analyze the managerial capability of madrasah principals in the decision-making process and to identify the factors that influence it within the context of Islamic education. A qualitative approach with a descriptive design was employed, with data collected through in-depth interviews, participatory observation, and document studies involving the principal and teaching staff at MTs Al-Amanah Al-Gontory. Data credibility was tested using source and method triangulation, while data analysis was conducted thematically through the stages of data reduction, data display, and conclusion drawing. The findings show that the principal’s managerial capability is relatively strong in the areas of planning, organizing, implementation, and supervision. Decision-making processes are carried out in a participatory manner through musyawarah with teachers, taking into account emotional stability, Islamic leadership values, and institutional sustainability. These findings indicate that strengthening the managerial competence of madrasah principals contributes significantly to decision quality and institutional climate. The study underscores the importance of developing managerial leadership rooted in Islamic values to enhance the effectiveness of madrasah governance in responding to contemporary educational dynamics.